Judicial Impartiality and Independence in Divided Societies: An Empirical Analysis of the Constitutional Court of Bosnia‐Herzegovina. Issue 4 (7th November 2016) - Schwartz, Alex; Janelle Murchison, Melanie
Abstract : The role of constitutional courts in deeply divided societies is complicated by the danger that the salient societal cleavages may influence judicial decision‐making and, consequently, undermine judicial impartiality and independence. With reference to the decisions of the Constitutional Court of Bosnia‐Herzegovina, this article investigates the influence of ethno‐national affiliation on judicial behaviour and the extent to which variation in judicial tenure amplifies or dampens that influence. Based on a statistical analysis of an original dataset of the Court's decisions, we find that the judges do in fact divide predictably along ethno‐national lines, at least in certain types of cases, and that these divisions cannot be reduced to a residual loyalty to their appointing political parties. Contrary to some theoretical expectations, however, we find that long‐term tenure does little to dampen the influence of ethno‐national affiliation on judicial behaviour. Moreover, our findings suggest that this influence may actually increase as a judge acclimates to the dynamics of a divided court. We conclude by considering how alternative arrangements for the selection and tenure of judges might help to ameliorate this problem.